Problemas Auditivos presentes en los niños de los Centros Educativos, ubicados en zonas con altos niveles de ruido en la ciudad de Loja, en relación a los niños que no estan expuestos a este riesgo. - Veintimilla Álvarez, Yolanda (2013)
The sense of hearing is an essential function for communication between people, learning, information exchange and identification of pleasant sounds and alert to situation so frisk, so the deficit is very important to know and demand for research prevention and necessary to preserve normal hearing. The present investigation seeks to determine whether the high levels of noise can cause hearing health problems in children. The field work was conducted in four and four schools not exposed to noise located in the central sector and peripheral sector according to the noise map of the Loja city, in each one schools average levels of noise were analyzed to compare with the provisions of environmental legislation. Additionally audiometric examination was performed to three hundred eighty (380) children to determine the levels of hearing loss. From the results obtained it was found that in the peripheral schools of the Loja city to be little vehicular sound pressure is less than 65dB, the permissible limit Ecuadorian legislation. While in the schools that are located in the central sector of Loja city the sound pressure exceeds the permissible limit of 65 dB, directly related to high vehicular traffic. Finally it can be shown that peripheral sector schools of the city there are no problems of hearing loss in children, unlike schools in the central sector of the noise levels, children have hearing problems light to moderate. We conclude that children studying in schools exposed to high noise levels present greater problems in their hearing with respect to their counter parts studying in schools located in areas without such noise levels.